[2-(4-Chlorophenyl)-5-phenyloxolan-3-yl](cyclopentenyl)methanone - Lee, Jae Kyun (International Union of Crystallography, 2011)
In the title compound, C(22)H(21)ClO(2), the oxolane ring adopts a twisted conformation. The dihedral angles between the mean plane of the oxolane ring and the mean planes of the 4-chlorophenyl, phenyl and cyclopentenyl rings are 71.81 (18), 76.9 (18) and 82.08 (18)°, respectively.